2017
DOI: 10.1097/qai.0000000000001442
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: CYP2B6 516G>T Minor Allele Protective of Late Virologic Failure in Efavirenz-Treated HIV-Infected Patients in Botswana

Abstract: Background CYPB2B6 polymorphisms that affect efavirenz (EFV) concentrations are common, but the effect of this polymorphism on HIV virologic failure in clinical practice settings has not fully been elucidated. Our objective was to investigate the relationship between the CYPB2B6 516G>T genotype and late virologic failure in patients treated with EFV in Gaborone, Botswana. Setting We performed a case-control study that included 1,338 HIV-infected black Batswana on EFV-based antiretroviral therapy (ART). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Pharmacogenetic studies of EFV and NVP have mostly been based on the CYP2B6 516G>T and 983T>C SNPs, with little or no clear assessment of the impact of the CYP2B6 785A>G and −82T>C SNPs. 14 Studies from Botswana on HIV patients taking EFV-based ART showed that the CYP2B6 516T allele was protective against 1-year, 29 but not at 6-months, 30 virologic breakthrough. However, no HIV DRMs have been assessed in either study.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenetic studies of EFV and NVP have mostly been based on the CYP2B6 516G>T and 983T>C SNPs, with little or no clear assessment of the impact of the CYP2B6 785A>G and −82T>C SNPs. 14 Studies from Botswana on HIV patients taking EFV-based ART showed that the CYP2B6 516T allele was protective against 1-year, 29 but not at 6-months, 30 virologic breakthrough. However, no HIV DRMs have been assessed in either study.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the current study is restricted to an average follow-up time of 6 months, and so questions regarding the impact of these polymorphisms in the response to therapeutic drugs and the long-term virologic and immunological response in this population remain to be answered. However, in a follow-up study in Botswana we observed that the CYP2B6 516G>T polymorphism showed a protective association with regards to the maintenance of HIV suppression [ 14 ]. Finally, in this exploratory analysis evaluating a total of 21 SNPs we cannot exclude that these findings were not due to chance and therefore future replication is essential to establish the validity of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although two-way messaging has been shown to be effective in treatment-naive individuals, treatment-experienced individuals pose a potentially greater challenge. Although treatment failure can be due to drug stockouts, 12 drug-drug interactions, 13 drug metabolism, 14,15 and pre-existing viral resistance, 16,17 populations with repeated treatment failures are likely to have a high number of individuals with repeated non-adherence. 18 Therefore, we aimed to find out if an intervention consisting of a two-way messaging system, with offers of local adherence support for individuals who requested help or who were not engaged with the system, would result in better HIV treatment outcomes than standard- of-care adherence support.…”
Section: Introductionmentioning
confidence: 99%